Adaptação transcultural da Bullying Scale para estudantes universitários brasileiros - Gonçalves, Naiane Glaciele da Costa (2019)
Bullying is a relationship issue that occurs in an intentional and repetitive way, consituting in a form of violence. It may occur through insults, threats and psychological or physical aggression, which can result on students’ emotional unbalance. This study aimed to develop a transcultural adaptation of the Bullying Scale for Brazilian Portuguese in three subscales: Bystander, Victim and Agressor. Each of them is composed by three factors Verbal Bullying, Emotional Bullying and Cyberbullying. We developed a methodological study in which the transcultural adaptation protocol comprehended equivalences of: concepts and items, semantics, applicability, measurements and functions. Initially, we developed the steps of translation, back translation, consensus, and agreement by the original author, specialists’ comitee and pre-test. Afterwards, we evaluated the psychometric propetites of the adapted scale. Population was composed by undergraduate students in a public university in Rio Grande do Sul, Brazil. Inclusion criteria were: age over 18 and regularly enrolled on the presential undergraduate course in the main campus of the referred university. Those that were on partially enrolled or who were on hiatus due to exchange programs in the country or abroad were excluded. Data collection happened between May and September 2019, through online questionnaire, containing 71 questions from Bullying Scale related to the Bystander, the Victim and the Aggressor; and questions that covered demographic and academic characterization. Data analysis was performed through descriptive and multivaried statistics. Bullying Scale – Brazil was submitted through evaluation of psychometric properties through reliability test and pretest, confirmatory and exploratory factorial analysis, convergent and discriminant validity. Global agreement on test and pretest was analyzed by the Prevalence and Bias Ajusted Kappa. To perform factorial analysis, we used Geomin rotation WLSMV estimator, available on the statistics package Mplus®, version 7.1 and in the R®. Research was approved by the Research Ethics Committee (Opinion Number 2.823.411). In the pretest, the scale items presented a compression > 90%. After the adaptation process, 2048 university students participated in the study. Of these, 192 participated in the retest. The test-retest showed temporal stability and agreement between the items (0.82 to 1.00). After excluding the blank questionnaires, the sample consisted of 1853 students. The adapted Bullying Scale was analyzed based on 71 of the three subscales. Exploratory analysis indicated the exclusion of one item related to the Spectator and 7 items related to the Victim. Aggressor subscale has been tested in several ways. However, the combination of items in the same factor did not present theoretical coherence. In this case, we chose to follow the original model. Excluding the suggested items, the Bullying Scale - Brazil consisted of 63 items (22 by the Spectator in four factors, 16 by the Victim in three factors and 25 by the Aggressor in three factors). In the sample studied, the Bullying Scale - Brazil proved to be valid, reliable and reliable. Future studies on scale performance in different Brazilian university contexts will be important.